PENGARUH PERPUTARAN MODAL KERJA, KEBIJAKAN PIUTANG DAN EFISIENSI OPERASIONAL TERHADAP UKURAN PERUSAHAAN PADA PT INDOFOOD CBP SUKSES MAKMUR TBK (ICBP) PERIODE 2015-2024 - Linka Medialara; Dina Novita (JURNAL RUMPUN MANAJEMEN DAN EKONOMI, 2026)
This study aims to analyze the effect of Working Capital Turnover, Accounts Receivable Policy, and Operational Efficiency on Firm Size at PT Indofood CBP Sukses Makmur Tbk during the period 2015–2024. The research method employed is a descriptive quantitative method with an associative approach. The data used are secondary data in the form of annual financial statements, with the research sample consisting of statements of financial position and income statements during the research period. Data analysis techniques include classical assumption tests, multiple linear regression analysis, coefficient of determination, as well as hypothesis testing using the t-test and F-test. The results of the t-test indicate that Working Capital Turnover does not have a significant effect on Firm Size with a significance value of 0.198>0.05, and Accounts Receivable Policy also does not have a significant effect with a significance value of 0.927>0.05. Meanwhile, Operational Efficiency has a significant effect on Firm Size with a significance value of 0.000<0.05. The F-test results show that the three variables simultaneously have a significant effect on Firm Size with a significance value of 0.000<0.05. The R Square value of 0.978 and the Adjusted R Square value of 0.967 indicate that the regression model has a very high level of accuracy.